TEACHING VOCABULARY BY USING ENGLISH COMIC TO IMPROVE VOCABULARY MASTERY - Erina, Rini; Salam, Urai; Husin, Sy. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purposes of this research are; (1) The use of English comic effective to improve the vocabulary and (2) How effective the use of English comic to improve vocabulary. The Researcher conducted a Pre â€“ Experimetal study using written test as tool of collecting data. The sample of this study 35 students on the seventh grades of SMP Negeri 6 Pontianak. The finding showed that the mean score of pre â€“ test was 54.71; which is categorized as â€œpoor to avarageâ€œ. Meanwhile, the mean score of post â€“ test was 79.28; which is categorized as â€œaverage to goodâ€. Based on tha data analysis, it was found that effect size of this research was 1.80 and it was categorized â€œHigh Effectâ€œ. It can be concluded thatthe teaching vocabulary by using English comic was effective to improve vocabulary mastery.Â Keywords:Teaching vocabulary, English comic, Pre â€“ Experimental